2021
DOI: 10.3390/jcm10040856
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Endogenous Retroelements in the Etiopathogenesis of Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus (SLE) is a heterogeneous autoimmune disease. While its etiology remains elusive, current understanding suggests a multifactorial process with contributions by genetic, immunologic, hormonal, and environmental factors. A hypothesis that combines several of these factors proposes that genomic elements, the L1 retrotransposons, are instrumental in SLE pathogenesis. L1 retroelements are transcriptionally activated in SLE and produce two proteins, ORF1p and ORF2p, which are immunogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 170 publications
0
17
0
Order By: Relevance
“…Retrotransposition-associated diseases Even with the transcriptional repression of L1s by the host, some L1s can still escape epigenetic silencing, leading to relatively high expression under certain circumstances. These include: (1) global DNA hypomethylation that usually occurs with aging (reviewed by Unnikrishnan et al, 2018); (2) local DNA hypomethylation and/or loss of histone repressive marks in the L1 promoter regions, which are typically found in cancer cells (Thayer et al, 1993;Alves et al, 1996;Shukla et al, 2013;Tubio et al, 2014;Scott et al, 2016;Burns, 2017Burns, , 2020; and (3) deregulation or mutations of L1 inhibitors, described in previous sections. Since L1 retrotransposition generates de novo insertions of L1 cDNA sequences into the genome, it could be harmful to genomic integrity, especially in the case of exonic insertions.…”
Section: L1 and Human Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrotransposition-associated diseases Even with the transcriptional repression of L1s by the host, some L1s can still escape epigenetic silencing, leading to relatively high expression under certain circumstances. These include: (1) global DNA hypomethylation that usually occurs with aging (reviewed by Unnikrishnan et al, 2018); (2) local DNA hypomethylation and/or loss of histone repressive marks in the L1 promoter regions, which are typically found in cancer cells (Thayer et al, 1993;Alves et al, 1996;Shukla et al, 2013;Tubio et al, 2014;Scott et al, 2016;Burns, 2017Burns, , 2020; and (3) deregulation or mutations of L1 inhibitors, described in previous sections. Since L1 retrotransposition generates de novo insertions of L1 cDNA sequences into the genome, it could be harmful to genomic integrity, especially in the case of exonic insertions.…”
Section: L1 and Human Diseasesmentioning
confidence: 99%
“…Subsequently, detection of the cytokines by their respective receptors (e.g., IFNAR in the case of type I IFN) will lead to the upregulation of ISGs, collectively also known as IFN signatures, which function to inhibit viral replication. Although the type I IFN response is vital for host protection against pathogens, aberrant chronic and/or episodic activation of type I IFN is known as a hallmark in many autoimmune diseases such as AGS, systemic lupus erythematosus (SLE) and Sjögren syndrome (SS) (Ivashkiv and Donlin, 2014;Tsokos et al, 2016;Crow et al, 2019;Ukadike and Mustelin, 2021).…”
Section: L1 and Human Diseasesmentioning
confidence: 99%
“…Immunogenic ORF1p and ORF2p proteins are produced by L1 retroelements, which causes generation of type I IFN. Additionally, ORF1p and ORF2p take place in RNA-rich macromolecular structures including SLE autoantigens such as Ro60, a 60 kDa RNA-binding protein [5,19,20]. Expression of at least one of the L1 proteins in the organs affected in SLE was demonstrated.…”
Section: Slementioning
confidence: 99%
“…About half of the human genome consists of retroelements but the majority of them acquired mutations since they are not under positive selection pressures during evolutionary processes, and these altered retroelements become inactive. However, many HERVs are still found having original functions [1,5]. Particular developmental stages, aging, inflammation and various pathologies can activate HERVs [6].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, in SLE, increased apoptosis or suboptimal clearance leads to an increase in autoantigen-antibody complexes, which have been shown to be endogenous IFN inducers and can continue to produce IFN, forming a vicious circle (5). When the immune system is activated and fights viral infection, IFN is a crucial cytokine in the onset and progression of SLE (6)(7)(8). Extensive data have found that all childhood SLE and more than 65% of adult SLE are clearly associated with IFN, IFN-producing cells, and IFNinduced products (9,10).…”
Section: Introductionmentioning
confidence: 99%